2018
DOI: 10.1371/journal.pone.0203402
|View full text |Cite
|
Sign up to set email alerts
|

EGFR signaling suppresses type 1 cytokine-induced T-cell attracting chemokine secretion in head and neck cancer

Abstract: Resistance to antitumor immunity can be promoted by the oncogenic pathways operational in human cancers, including the epidermal growth factor receptor (EGFR) pathway. Here we studied if and how EGFR downstream signaling in head and neck squamous cell carcinoma (HNSCC) can affect the attraction of immune cells. HPV-negative and HPV-positive HNSCC cell lines were analyzed in vitro for CCL2, CCL5, CXCL9, CXCL10, IL-6 and IL-1β expression and the attraction of T cells under different conditions, including cetuxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 43 publications
1
16
0
1
Order By: Relevance
“…There are in theory several rationales for co-targeting EGFR on tumor cells and PD1 on T cells via a BsAb: 1) accumulating evidence demonstrated that stimulation of EGFR signaling can suppress immune responses and enhance the tumor cell evasion of immune surveillance, including induction of PDL-1 overexpression on the surface of tumor cells, stimulation of VEGF, IL6, IL10 secretion, activation of regulatory T cells (Tregs) and downregulation of T cell chemokines [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] . Inhibition of EGFR signaling in tumor cells, therefore, not only can exert direct antitumor activity but also may create a more favorable anti-tumor immune microenvironment [40 , 46] ; 2) By targeting EGFR-overexpressing tumor cells, anti-PD1 x EGFR BsAb may enhance the antibody localization to specifically target and activate T cells and other immune cells within the tumor microenvironment [29] ; 3) the BsAb simultaneously targeting EGFR on tumor cell surface and PD1 on T cells may likely be able to create direct cell-cell interaction/engagement of the tumor cells and the immune cells, and leads to the formation of immunological synapse, resulting in CD8 + T cell activation and potent tumor cell killing [30 , 47] .…”
Section: Discussionmentioning
confidence: 99%
“…There are in theory several rationales for co-targeting EGFR on tumor cells and PD1 on T cells via a BsAb: 1) accumulating evidence demonstrated that stimulation of EGFR signaling can suppress immune responses and enhance the tumor cell evasion of immune surveillance, including induction of PDL-1 overexpression on the surface of tumor cells, stimulation of VEGF, IL6, IL10 secretion, activation of regulatory T cells (Tregs) and downregulation of T cell chemokines [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] . Inhibition of EGFR signaling in tumor cells, therefore, not only can exert direct antitumor activity but also may create a more favorable anti-tumor immune microenvironment [40 , 46] ; 2) By targeting EGFR-overexpressing tumor cells, anti-PD1 x EGFR BsAb may enhance the antibody localization to specifically target and activate T cells and other immune cells within the tumor microenvironment [29] ; 3) the BsAb simultaneously targeting EGFR on tumor cell surface and PD1 on T cells may likely be able to create direct cell-cell interaction/engagement of the tumor cells and the immune cells, and leads to the formation of immunological synapse, resulting in CD8 + T cell activation and potent tumor cell killing [30 , 47] .…”
Section: Discussionmentioning
confidence: 99%
“…EGFR can promote tumor cell proliferation, metastasis, anti-apoptosis and angiogenesis by activating its downstream signaling pathways Ras/Raf/MEK/ERK and phosphatidylinositide 3-kinases/protein kinase B (PI3K/Akt) [45,46]. Some studies reported that EGFR also could promote the tumor immune escape mechanism [47,48]. In recent years, EGFR-targeted therapy has been used to clinical treatment of OSCC [49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…A study found a number of tumor immunity-related inflammatory cells, for example, cytotoxic T cells (CTLs), regulatory T cells (Tregs), myeloid-derived suppressor cells (MDSCs), and natural killer (NK) cells (37). It also found a number of tumor immunity-related pathways, such as altered interleukin signaling (117), MHC-I pathway (118), type 1 cytokine-induced T-cell (119), interferon gamma signaling (120), type I interferon-mediated responses (121), and transcription factor nuclear factor-kappa B (122). Along with the advancement in tumor immunology, the immune-checkpoint blockade therapy has been an important aspect in the mode of combined therapy of tumor.…”
Section: Mitochondrial Dysfunction-mediated Tumor Immunitymentioning
confidence: 99%